Origin of Conservation Refugees The Downside of Environment Protection in India - Kurian, Anju Lis; Muñoz-Telles , John Maximino; Bernal-Gomez, Daniel Rigoberto; Vinodan, C (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The conservation of biodiversity and natural resources can help offer a sustainable supply of goods and services to fulfil the right of people to development and livelihood. However, the conservation record is not inspiring in India and across the world, when its social, economic, and cultural impacts on local people are considered. Conservation projects that exclude local people may conserve natural resources to an extent but not people’s access to livelihoods. By being a densely populated country, India cannot encourage the strategy of “pristine nature” in its conservation initiatives.